MEMBEDAH FAKTOR PENENTU KEBERHASILAN PROSES DAN HASIL BELAJAR - Harif Rahman Suyatno; Afnibar; Ulfatmi (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This study aims to examine the factors influencing the learning process and outcomes through four main aspects: raw input, process instrumental, output, and outcome. Raw input includes the physical, intellectual, psychological, and social conditions of students, while process instrumental covers curriculum, teacher roles, teaching methods, and learning media. Output refers to cognitive, affective, and psychomotor achievements, whereas outcome emphasizes long-term impacts such as work readiness, social relevance, and character development. This study also highlights critical thinking skills, learning strategies, and the theory of multiple intelligences, which align with the concept of fitrah in Islam. From an Islamic perspective, intention, sincerity, environment, and religious motivation are key factors influencing learning success. Thus, learning outcomes are viewed as an integration of intellectual, social, and spiritual dimensions.